PENERAPAN ASUHAN LANSIA TERPADU (ICOPE) DI DESA SESETAN KECAMATAN DENPASAR SELATAN BALI - Aryana, I.G.P.S.; Kuswardhani, R.A.T.; Astika, I.N.; Putrawan, I.B.P.; Purnami, N.K.R.; Triningrat, A.A.M.P.; Putra, I.D.G.A.E.; Diniari, N.K.S.; Widyastuti, K. (Buletin Udayana Mengabdi, 2023)
In the aging process, the functional ability of the elderly begins to decline. Health workers and elderly cadres are expected to be able to identify parents who have decreased functional abilities and provide appropriate care to treat or slow down the loss of functional abilities by using an integrated care approach for the elderly. The purpose of this service activity is to increase the knowledge of elderly cadres related to integrated elderly care (ICOPE). The method of implementing the activity is giving pre-test questions at the beginning of the training and post-test at the end of the activity. The training was carried out online considering that the Covid-19 pandemic situation was still ongoing. The training was attended by 46 elderly cadres in the Work Area of Puskesmas 1 South Denpasar. Based on age category, 65.22% of participants were aged 41-50 years and all participants were female. Most of the training participants' education was SMA as many as 29 people (63.04%). Of the 46 participants, 31 participants took the pre-test and post-test, 15 other participants experienced problems when taking the pre-test and post-test, one of which was still confused about using gadgets. From the evaluation results, it was found that the average pre-test score increased to 65 and the posttest score increased to 71. The training went well and effectively increased the knowledge of elderly cadres related to integrated elderly care (ICOPE). Keywords : elderly, integrated care for the elderly, functional ability